HUMANITARIAN DEMINING IN UKRAINE: STATE POLICY AND PUBLIC ADMINISTRATION - Boyko, Oksana; Haman, Petro; Pavlov, Sergiy (Public Management and Policy, 2025)
The article considers the issues of organizing humanitarian demining in Ukraine, the formation and implementation of state policy in this area, the structure of state administration in this area of activity, and the improvement of mine action in view of the scale of related challenges. The relevance of the study is due to the fact that as a result of the full-scale Russian invasion of Ukraine, about 30 % of its territory is contaminated with explosives. The purpose of the study is to analyze the issues of organizing humanitarian demining under martial law, scientifically substantiate approaches to the further organization of humanitarian demining, improve state policy and state administration, and national legislation in this area. Among the issues analyzed in the article are: regulatory and legal support for humanitarian demining, the functioning of mine action entities defined by current national legislation, in particular the National Authority for Mine Action, the role of central and local executive authorities in this area of activity. A noticeable increase in the number of scientific studies on the implementation of demining work (humanitarian demining) has been noted. The authors of the article analyzed a number of scientific works, in particular on the development of effective methods and technologies for demining, restoration and socio-economic rehabilitation of contaminated areas. During the study, theoretical methods such as systemic and comparative analysis, synthesis, and classification methods were used. The results of the study proved the need for further improvement of the regulatory framework in the field of humanitarian demining, strengthening work with mine action operators, digitalization of the process of their certification, expansion of international cooperation in the field of humanitarian demining, in particular regarding the technical equipment of pyrotechnic units, training of specialists in the field of mine action, and educating the population about the risks associated with explosive objects. The priority tasks are the implementation of the National Mine Action Strategy for the period until 2033 and the operational plan of measures for its implementation in 2024–2026, the search for effective ways to reduce the negative impact of explosive contamination on the environment, and the expansion of international cooperation within the framework of the European Union Civil Protection Mechanism.